The development of an integrated neighborhood approach for health promotion and prevention: a qualitative exploration of stakeholders' views - Anniek Bosdijk; Anna Petra Nieboer; Jane Murray Cramm (BMC, 2023)
Abstract Background Although the promise of integrated neighborhood approaches, including the essential roles of communities and collaboration between the medical and social domains, has been widely acknowledged, the realization of such approaches in practice often remains difficult. To gain insight into the development of integrated neighborhood approaches, this case study describes the experiences of stakeholders involved in such an approach for health promotion and prevention in Rotterdam. Methods Interviews with 18 stakeholders (including health and social care professionals, health insurance employees, and policymakers) were conducted, and stakeholders' statements were analyzed thematically. Results The results reveal a lack of alignment among the professional, organizational, and system levels. Elements needed for collaboration between health and social care professionals are not supported at the organizational and system levels. The lack of integration at the policy and organizational levels encourages competition and self-interest instead of stimulating collaboration. Conclusions Intersectoral collaboration and coordination must take place not only between professionals, but also at the organizational and policy levels. As long as integration at the organizational and system levels is lacking, professionals' ability to collaborate and provide coordinated support to neighborhood residents will be compromised.